A polymer humidity sensor - Hwang, L.S.; Ko, J.M.; Rhee, H.W.; Kim, C.Y. (1993)
Polypyrrole doped with dodecylsulfate ion on electrochemical polymerization of pyrrole keeps the anion in it on reduction of the polymer in an aqueous solution. The free anion on reduction of the polymer attracts a cation to form a salt in the polymer. An attempt was made to use polypyrrole as a sensing material in measurement of humidity. The gold covered electrode was constructed by employing a photo-resist method and the ionic conductivity of the reduced polypyrrole changes from 2 × 10 kΩ·cm to 3 × 103 kΩ·cm depending on humidity. ？ 1993.
Keywords: Atmospheric humidity; Electrodes; Ionic conduction; Measurements; Sensors; Dodecylsulfate ion; Electrochemical polymerization; Humidity sensor; Polypyrrole; Polymers